Strategy for Empowering Micro, Small, and Medium Enterprises (MSMEs) Based on Local Potential - Widyanani Widyanani; Rakhmat Bakhtiar; Mita Marwiah (ijd-demos, 2024)
Abstract Community empowerment programs serve as strategic instruments for alleviating poverty and fostering rural economic self-reliance. This study aims to conduct an in-depth analysis of the implementation dynamics of community empowerment programs in Cikeusik District, Pandeglang Regency, and to map the factors that facilitate or hinder their effectiveness. A descriptive qualitative research approach was employed. Findings from the first section indicate that, while the implementation process proceeded structurally and bureaucratically through the *Musrenbang* (development planning forum), it suffered from information bottlenecks at the grassroots level and an actor disposition focused more on administrative compliance (outputs) than on sustainable impact (outcomes). Consequently, post-assistance monitoring weakened, leading to a phenomenon of business groups becoming dormant or inactive. The second section identifies abundant natural resources and strong social capital—specifically the spirit of *gotong royong* (mutual cooperation)—as key facilitating factors. Conversely, dominant inhibiting factors include the limited quality of human resources among program managers, meager capacity-building budgets, inter-agency sectoral ego, a community mentality of dependency, and damaged connecting infrastructure that drives up logistics costs. The study concludes that there is a need to reorient empowerment strategies—shifting from mere piecemeal material assistance toward a holistic, integrative approach that addresses issues continuously, spanning the entire value chain from upstream production to downstream marketing. Keywords: Policy Implementation, Community Empowerment, Facilitating Factors, Inhibiting Factors.